Dynamics of a Christian Minority within a Muslim-Majority Context: A Socio-Historical Study of Congko Village, Soppeng 1940–2024 - Al Haris All, Muh. Akhyar; Bahri, Bahri; Patahuddin, Patahuddin; Najamuddin, Najamuddin (Abrahamic Religions: Jurnal Studi Agama-Agama, 2026)
This study examines the socio-historical dynamics of the Christian community in Batu Pute hamlet, Congko Village, Soppeng Regency, South Sulawesi, within a predominantly Muslim Bugis society from 1940 to 2024. The research focuses on the processes of emergence, survival, and transformation of Christian minority identity within a Muslim-majority social structure. The main research questions address: (1) the socio-cultural and spiritual factors influencing religious conversion in Batu Pute; (2) forms of adaptation, resistance, and survival strategies developed by the Christian community in response to political and ideological pressures during the colonial period, the Japanese occupation, and the DI/TII rebellion; and (3) the reconstruction of social relations and collective identity in the post-conflict period through the New Order and Reformasi era. This study employs a qualitative socio-historical approach, utilizing in-depth interviews, archival research, and literature analysis. The findings reveal that Christianity in Batu Pute did not emerge as a result of colonial religious intervention, but rather developed through local initiatives shaped by spiritual experiences and the integration of Bugis cultural values, particularly the concept of Dewata SeuwaE as a monotheistic theological framework. During periods of political turmoil, the community experienced marginalization and structural pressures, yet demonstrated remarkable social and spiritual resilience. In the post-conflict era, interreligious reconciliation was fostered through the internalization of local ethical principles such as sipakatau (humanizing others), sipakalebbi (mutual respect), and sipakainge (mutual moral reminding), which functioned as social capital for rebuilding intercommunal harmony. This study argues that the integration of minority religious identity with local cultural values constitutes a powerful social foundation for peacebuilding, social cohesion, and community resilience in plural societies